Effect of high pressure pre-treatment on raw ewes’ milk and on subsequently produced cheese throughout ripening - Inácio, Rita S. (2022)
BACKGROUND: Raw ewe's milk, as used to manufacture Serra da Estrela Protected Designation of Origin cheese, was pre-treated y high pressure processing (HPP), using previously optimized conditions (121 MPa for 30 min), aiming to evaluate its effect on ilk technological properties for subsequent cheese production, namely the impact on resulting curd, whey and cheese hroughout ripening. RESULTS: The cheese yield increased 10.4% as a result of milk pre-treated by HPP, which also yielded inactivation of beneficial icrobial groups. After 60 days of ripening, both treated and control cheeses showed no significant differences (P ≥ 0.05) with espect to quantified microbial load or basic physicochemical quality parameters. CONCLUSION: HPP appears to be a promising non-thermal treatment for ewes' milk to inactivate contaminant bacteria but ith no negative effect on lactic acid bacteria, which is very important for the unique characteristics of Serra da Estrela cheese.